2019
DOI: 10.1038/s41586-019-0914-z
|View full text |Cite
|
Sign up to set email alerts
|

Directionality of dynein is controlled by the angle and length of its stalk

Abstract: The ability of cytoskeletal motors to move unidirectionally along filamentous tracks is central to their role in cargo transport, motility and cell division. While kinesin and myosin motor families have members that move in opposite directions 1 , 2 , all dyneins studied to date exclusively move towards the microtubule (MT) minus-end 3 . In order to understand the mechanism of dynein’s directionality, we sought to engineer a plus-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 35 publications
6
62
1
Order By: Relevance
“…The present model can be extended to study the effects of the vectorial character of the applied load on the mechanics of dynein and myosin motors, since the load-velocity and -detachment rate behaviours of kinesins, dyneins, and myosins are similar [14][15][16][17]. This can help to understand the mechanics of collective function of different molecular motors, owing to the force-dependent interactions of the motors.…”
Section: (C) and 3(b)mentioning
confidence: 94%
See 1 more Smart Citation
“…The present model can be extended to study the effects of the vectorial character of the applied load on the mechanics of dynein and myosin motors, since the load-velocity and -detachment rate behaviours of kinesins, dyneins, and myosins are similar [14][15][16][17]. This can help to understand the mechanics of collective function of different molecular motors, owing to the force-dependent interactions of the motors.…”
Section: (C) and 3(b)mentioning
confidence: 94%
“…They measured the vertical load component F z , where the horizontal component F x was resisting (<0, applied against the stepping direction). More recently, single-molecule optical trapping experiments [14][15][16][17] have studied the function of molecular motors under assisting loads F x (>0, applied in the stepping direction) as well. They have shown that the motors exhibit similar responses to the applied load direction: i) their velocity decreases with resisting loads, but changes slightly when the load is assisting, and ii) motors favor faster detachment rate under assisting loads than resisting ones.…”
Section: Introductionmentioning
confidence: 99%
“…In broad brushstrokes, cytoplasmic dynein motors can be divided into two sub-families: mammalian and yeast dynein, or weak and strong dynein (according to their characteristic stalling force (3,4)), respectively. There is a burgeoning interest in these motors (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), in particular, their mechanism of motion and regulation. However, dynein's stepping mechanism remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…However, dynein's stepping mechanism remains largely unknown. Furthermore, in recent years, evidence emerged that, unlike kinesin, yeast cytoplasmic dynein motors (henceforth referred to as "dynein") are not limited to steps that are parallel to the MT long axis (x-axis), and in fact, they perform steps in all directions, such as in the direction of the MT short axis (y-axis) (5)(6)(7). While our primary focus in this work is yeast dynein, some conclusions will be drawn regarding mammalian cytoplasmic dynein.…”
Section: Introductionmentioning
confidence: 99%
“…EM studies indicate that the dynein stalk in the MT-bound state tilts backward, with an angle of ~42º 32 . A recent study showed that the reverse kink mutant, which moves in the opposite direction, still possesses resistance to the minus-end force (i.e., as with the regular dynein motor) 33 , further supporting the binding mode of low-affinity MTBD and confirming that its interface geometry with respect to MTs is crucial for generating the directional preference of dynein motility.…”
Section: A Model Of Biased Movement Of Dyneinmentioning
confidence: 74%